Medicīnas studentu alkohola lietošanas paradumi, iemesli un iznākumi - Karabacak, Ersin (Latvijas Universitāte, 2025)
Background: According to the Organisation for Economic Co-operation and Development (OECD), Latvia has the highest alcohol consumption rate per capita among EU and OECD. This is why raising awareness and unveiling patterns of alcohol consumption, especially among medical students are vital for health outcomes and for the treatment of patients by physicians afterwards. Objectives: To determine the prevalence of alcohol consumption among medical students, investigating the frequency, causes and patterns and the outcomes in terms of academic performance. Materials and methods: The cross-sectional study was conducted anonymously as an online survey via “QuestionPro”. Data was collected from 02.10.2024 till 14.03.2025. The survey consisted of 4 parts: demographic information, Consumption patterns, reasons for consumption, perception, outcomes, and awareness. The participation was anonymously and voluntarily. The statistical analysis was made with IBM SPSS Statistics Version 29.0.0.0 (241). The statistical significance was defined as p < 0.05 and calculated with the Chi-Square test. Results: The study included 277 participants, predominantly female (74.2%). 49.8% students were from Latvia and 50.2% were non-Latvian students. Latvian students consume nicotine more frequently (p = 0.0020). The alcohol consumption remains frequent with 58.5%. Latvian students drink “once in two weeks” more frequently (p = 0.036). Binge drinking occurred with a high prevalence of 66.1% and with 16.3% of students engaging at least once a month. Latvian students prioritize the quality over price. Wine (70.8%), beer (48.4%), and vodka (39.0%) were most commonly consumed. Latvian students consume gin (p = 0.027) and champagne (p = 0.034) more frequent. Leading causes to consume alcohol were socializing (75.0%) and celebrations (73.6%). Students from Latvia were more likely to drink stress related. Social pressure to binge drink was common with 72.2% and 61.7% of students have experienced negative stigmatization when verbalizing not to drink. Potential carcinogenic effects and cardiovascular risks were accurately identified, while gaps for breast cancer, risks for head and neck cancer, atrial fibrillation, or myopathy were detected. 50.5% of students believed that no amount of alcohol is safe to consume. Latvian students reduce their consumption over the study years more commonly. Short-time side effects included headaches (74.0%), nausea (67.5%) and vomiting (57.0%). Latvian students experienced post-alcohol anxiety more frequently with 36.2% (p = 0.008). Long-term effects included sleep disturbances (17.1%), skin changes (15.6%) and lack of concentration (13.8%). Outcomes: The prevalence of alcohol consumption among medical students remains high, with a ranging consumption frequency. Overall moderate consumption was able to be identified. Binge drinking was commonly experienced. Higher alcohol consumption is associated with lower academic performance.

Pamatinformācija: Ekonomiskās sadarbības un attīstības organizācijas (ESAO) dati liecina, ka Latvijā ir visaugstākais alkohola patēriņa līmenis uz vienu iedzīvotāju ES un ESAO. Tāpēc izpratnes veicināšana un alkohola patēriņa modeļu atklāšana, īpaši medicīnas studentu vidū, ir ļoti svarīga veselības stāvokļa uzlabošanai un ārstu turpmākai pacientu ārstēšanai. Mērķi: Noskaidrot alkohola lietošanas izplatību medicīnas studentu vidū, izpētot alkohola lietošanas biežumu, cēloņus un modeļus, kā arī rezultātus attiecībā uz akadēmiskajiem sasniegumiem. Materiāli un metodes: Šķērsgriezuma pētījums tika veikts anonīmi kā tiešsaistes aptauja, izmantojot “QuestionPro”. Dati tika vākti no 02.10.2024. līdz 14.03.2025. Aptauja sastāvēja no 4 daļām: demogrāfiskā informācija, patēriņa modeļi, patēriņa iemesli, uztvere, rezultāti un informētība. Dalība aptaujā bija anonīma un brīvprātīga. Statistiskā analīze tika veikta, izmantojot IBM SPSS Statistics 29.0.0.0.0 versiju (241). Statistiskā nozīmība tika definēta kā p < 0,05 un aprēķināta ar Chi-Square testu. Rezultāti: Pētījumā piedalījās 277 dalībnieki, pārsvarā sievietes (74.2%). 49.8 % studentu bija no Latvijas un 50.2 % bija studenti no citām valstīm. Latvijas studenti biežāk lieto nikotīnu (p = 0.0020). Alkohola lietošana joprojām ir bieža – 58.5 %. Latvijas skolēni biežāk lieto alkoholu “reizi divās nedēļās” (p = 0.036). Alkohola pārmērīga lietošana ir sastopama ar augstu izplatību – 66.1 %, un vismaz reizi mēnesī to lieto 16,3 % skolēnu. Latvijas skolēni priekšroku dod kvalitātei, nevis cenai. Visbiežāk tika lietots vīns (70.8 %), alus (48.4 %) un degvīns (39.0 %). Latvijas skolēni biežāk lieto džinu (p = 0.027) un šampanieti (p = 0.034). Galvenie alkohola lietošanas iemesli bija socializēšanās (75.0 %) un svinības (73.6 %). Skolēni no Latvijas biežāk lietoja alkoholu, kas saistīts ar stresu. Sabiedrības spiediens dzert bija izplatīts 72.2 % un 61.7 % skolēnu ir piedzīvojuši negatīvu stigmatizāciju, verbalizējot, ka nedrīkst dzert. Tika precīzi identificēta iespējamā kancerogēnā ietekme un kardiovaskulārie riski, bet tika konstatētas nepilnības attiecībā uz krūts vēzi, galvas un kakla vēža, priekškambaru fibrilācijas vai miopātijas riskiem. 50.5 % skolēnu uzskatīja, ka nevienu alkohola daudzumu nav droši lietot. Latvijas skolēni pētījuma gados biežāk samazina alkohola patēriņu. Īslaicīgas blakusparādības bija galvassāpes (74.0%), slikta dūša (67.5%) un vemšana (57.0%). Latvijas skolēni biežāk izjuta trauksmi pēc alkohola lietošanas – 36.2 % (p = 0.008). Ilgtermiņa ietekme ietvēra miega traucējumus (17.1 %), ādas izmaiņas (15.6 %) un koncentrēšanās spēju trūkumu (13.8 %). Rezultāti: Alkohola patēriņa izplatība medicīnas studentu vidū joprojām ir augsta, un alkohola patēriņa biežums ir atšķirīgs. Kopumā izdevās noteikt mērenu alkohola patēriņu. Bieži tika novērota pārmērīga alkohola lietošana. Lielāks alkohola patēriņš ir saistīts ar zemākiem mācību rezultātiem.
Patterns, reasons, and outcomes of alcohol consumption among medical students
Keywords: Medicīna; Alcohol consumption; medical students; substance abuse; binge drinking; drinking habits